Role of the mitochondrial DNA 16184-16193 poly-C tract in type 2 diabetes. - Chinnery, P; Elliott, H; Patel, S; Lambert, C; Keers, S; Durham, SE; McCarthy, M; Hitman, G; Hattersley, A; Walker, M (2005)
Recent evidence suggests that polymorphic genetic variation in the non-coding region of mitochondrial DNA (the 16184-16193 polycytosine [poly-C] tract) contributes to the cause of type 2 diabetes, but previous studies only just reached significance. We aimed to investigate this association. We compared patients with type 2 diabetes (n=992) with two independent control groups (n=536, n=1029) from the UK, and saw no difference in the frequency of the 16184-16193 poly-C tract. This finding was confirmed by a meta-analysis of European studies of 1455 patients and 3132 controls (odds ratio 1.16, 95% CI 0.94-1.44). Genetic variation of the 16184-16193 poly-C tract is unlikely to have a major role in the cause of type 2 diabetes.